2007
DOI: 10.1038/sj.jcbfm.9600570
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate and Univariate Analysis of Continuous Arterial Spin Labeling Perfusion MRI in Alzheimer's Disease

Abstract: Continuous arterial spin labeling (CASL) magnetic resonance imaging (MRI) was combined with multivariate analysis for detection of an Alzheimer's disease (AD)-related cerebral blood flow (CBF) covariance pattern. Whole-brain resting CBF maps were obtained using spin echo, echo planar imaging (SE-EPI) CASL in patients with mild AD (n = 12, age = 70.7 ± 8.7 years, 7 males, modified Mini-Mental State Examination (mMMS) = 38.7/57 ± 11.1) and age-matched healthy controls (HC) (n = 20; age = 72.1 ± 6.5 years, 8 male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
132
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 149 publications
(145 citation statements)
references
References 30 publications
10
132
1
Order By: Relevance
“…The present findings indicate that these changes are not simply late‐stage manifestations of AD but are demonstrable even in early AD (ie, in Braak stage III–IV disease) in the precuneus, a region that is amongst the first affected by hypoperfusion 2, 6, 7, 13, 28, 30, 53. Indeed, the MAG:PLP1 ratio, an indicator of the adequacy of ante‐mortem tissue oxygenation, was lower in early than late AD (Braak stage V–VI) when the reduction was less pronounced, possibly reflecting falling oxygen demand, for example, as a result of reduced synaptic activity.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…The present findings indicate that these changes are not simply late‐stage manifestations of AD but are demonstrable even in early AD (ie, in Braak stage III–IV disease) in the precuneus, a region that is amongst the first affected by hypoperfusion 2, 6, 7, 13, 28, 30, 53. Indeed, the MAG:PLP1 ratio, an indicator of the adequacy of ante‐mortem tissue oxygenation, was lower in early than late AD (Braak stage V–VI) when the reduction was less pronounced, possibly reflecting falling oxygen demand, for example, as a result of reduced synaptic activity.…”
Section: Discussionmentioning
confidence: 55%
“…Blood flow and glucose utilization decline in the precuneus at a very early stage of Alzheimer's disease (AD) 2, 6, 7, 13, 28, 30, 53. Reduction in cerebral blood flow precedes the development of dementia in AD 52 and occurs well before any behavioral or pathological abnormalities in animal models of the disease 24, 39.…”
Section: Introductionmentioning
confidence: 99%
“…The pattern of hypoperfusion revealed in our study is consistent with the patterns found in the previous ASL and PET studies, although hypoperfusion in the lateral parietal lobe did not show up. A very recent report by Asllani et al [22] showed that ASL at 1.5-T MR imaging combined with multivariate analysis can differentiate 12 AD patients from 20 healthy control subjects at a high AUC value in ROC analysis. Our result was consistent with theirs, although we used only univariate analysis.…”
Section: Discussionmentioning
confidence: 97%
“…13 Although many recent ASL perfusion studies were performed on 3T MR imaging, it has been shown in other studies that ASL with 1.5T MR imaging could detect regional hypoperfusion, mainly in the temporoparietal association cortex and the posterior cingulate gyrus. 8,10,25 Another study suggested that CBF mapping by ASL may perform better than MR morphologic analysis by using voxel-based morphometry in discriminating patients with AD from healthy control subjects and that the combination of the 2 methods was more effective than either method alone. 26 This result may support our proposal for the combination of structural MR imaging and ASL MR perfusion imaging.…”
Section: Discussionmentioning
confidence: 99%